Copy Number Analysis Reveal Genetic Risks of Penile Cancer - Yu, Yongbo; Gao, Chengwen; Chen, Yuanbin; Wang, Meilan; Zhang, Jianfeng; Ma, Xiaocheng; Liu, Shuaihong; Yuan, Hang; Li, Zhiqiang; Niu, Haitao (Frontiers in Oncology, 2020)
Objectives To evaluate copy number alterations (CNAs) in genes associated with penile cancer (PeC) and determine their correlation and prognostic ability with PeC. Methods Whole-exome sequencing was performed for tumor tissue and matched normal DNA of 35 patients diagnosed with penile squamous cell carcinoma from 2011 to 2016. Somatic CNAs were detected using the Genome Analysis Toolkit (GATK). Retrospective clinical data were collected and analyzed. All the data were statistically analyzed using SPSS 16.0 software. The cancer-specific survival rates were estimated by Kaplan-Meier curves and compared with the log-rank test. Results CNAs in the MYCN gene was detected in 19 (amplification: 54.29%) patients. Other CNAs gene targets were FAK (amplification: 45.72%, deletion: 8.57%), TP53 (amplification: 2.86%, deletion: 51.43%), TRKA (amplification: 34.29%, deletion: 2.86%), p75NTR (amplification: 5.71%, deletion: 42.86%), Miz-1 (amplification: 14.29%, deletion: 20.00%), Max (amplification: 17.14%, deletion: 2.86%), Bmi1 (amplification:14.29%, deletion: 48.57%), and MDM2 (amplification: 5.71%, deletion: 45.72%). The CNAs in MYCN and FAK correlated significantly with patient prognosis (P<0.05). The 3-year Recurrence-free survival rate was 87.10% among patients followed up. The 5-year survival rate of patients with MYCN amplification was 69.2%, compared to 94.4% in the non-amplification group. The 5-year survival rate of patients with FAK amplification was 65.6%, compared to 94.7% in the non-amplification group. The PPI network showed that TP53 and MYCN might play meaningful functional roles in PeC. Conclusion MYCN and FAK amplification and TP53 deletion were apparent in PeC. MYCN and TP53 were hub genes in PeC. MYCN and FAK amplification was also detected and analyzed, and the findings indicated that these two genes are predictors of poor prognosis in PeC.